2008
DOI: 10.1177/0272989x08315235
|View full text |Cite
|
Sign up to set email alerts
|

Wide Social Participation in Prioritizing Patients on Waiting Lists for Joint Replacement: A Conjoint Analysis

Abstract: Both clinical and social criteria are considered for prioritization of joint replacement surgery from a wide social perspective. The preference among professional and social groups varies and this might impact the result of patient prioritization. A wide social participation for obtaining adequate prioritizing systems for patients on waiting lists is desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The main weaknesses are that a certain amount of agreement must already exist in participating members and the amount of time necessary to prepare and execute the technique in each focus group. The method described in this paper has been used to develop criteria for consideration in other health care studies [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…The main weaknesses are that a certain amount of agreement must already exist in participating members and the amount of time necessary to prepare and execute the technique in each focus group. The method described in this paper has been used to develop criteria for consideration in other health care studies [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…It could also be argued that this tool does not include patients' views when deciding on weights. Previous literature (20) has shown that patients tend to give more weight to those criteria that have a close relation with patient-related issues (e.g., pain). Because the weight attributed to patient-related aspects is already high in our study, we understand this limitation has been minimized here.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, this method has gained widespread use in the health and medical setting in eliciting preferences for healthcare [21][23]. The theory behind CA is that any product (goods or services) can be described by a set of characteristics and the extent to which an individual places value on a product is determined by the level of those separate characteristics (part-worth of the product) and the combination of those characteristics (overall worth of the product) [21], [22], [24].…”
Section: Introductionmentioning
confidence: 99%